Practical implementation of an interior point nonmonotone line search filter method - Costa, M. Fernanda P. (2008)
Here we present a primal-dual interior point nonmonotone line search filter method for nonlinear programming. The filter relies on three measures, the feasibility, the centrality and the optimality presented in the optimality conditions, considers relaxed acceptability criteria for the step size and includes a feasibility restoration phase. The evaluation of the method is until now made on small problems and a comparison is provided with a merit function approach.